Conceptualization of the ambidextrous organization: From the perspective of dynamic capabilities (2017)
The variety of conceptual and operational definitions of the ambidextrous organization limits the development of the theory and the empirical results comparisons. Provides a heuristic based on the latent characteristics and longevity, with respect to the conceptualization of the Ambidextrous organization from the exploration and exploitation. Then, identify a stipulative definition with established criteria, in a way that serves to further research that foster the improvement of the definition. © 2017.